2018
DOI: 10.1016/j.jaut.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of loci where DNA methylation potentially mediates genetic risk of type 1 diabetes

Abstract: The risk of Type 1 Diabetes (T1D) comprises both genetic and environmental components. We investigated whether genetic susceptibility to T1D could be mediated by changes in DNA methylation, an epigenetic mechanism that potentially plays a role in autoimmune diabetes. From enrichment analysis, we found that there was a common genetic influence for both DNA methylation and T1D across the genome, implying that methylation could be either on the causal pathway to T1D or a non-causal biomarker of T1D genetic risk. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 56 publications
(65 reference statements)
1
17
0
Order By: Relevance
“…The findings from our study show increased methylation levels in the dmCpGs within the body of AFF3 in the individuals with T1D-ESKD, which could result in decreased gene expression. A link between DNA methylation of this gene and T1DM has previously been considered as a mediator of the genetic risk [83]. Each of the top-ranked dmCpGs identified from this analysis were present within the body of AFF3 with increased methylation in individuals with T1DM-ESKD.…”
Section: Discussionmentioning
confidence: 85%
“…The findings from our study show increased methylation levels in the dmCpGs within the body of AFF3 in the individuals with T1D-ESKD, which could result in decreased gene expression. A link between DNA methylation of this gene and T1DM has previously been considered as a mediator of the genetic risk [83]. Each of the top-ranked dmCpGs identified from this analysis were present within the body of AFF3 with increased methylation in individuals with T1DM-ESKD.…”
Section: Discussionmentioning
confidence: 85%
“…The findings from our study show increased methylation levels in the dmCpGs within the body of AFF3 in the individuals with T1D-ESKD, which could result in decreased gene expression. A link between DNA methylation of this gene and T1DM has previously been considered as a mediator of the genetic risk (97). Each of the top-ranked dmCpGs identified from this analysis were present within the body of AFF3 with increased methylation in individuals with T1DM-ESKD.…”
Section: Discussionmentioning
confidence: 85%
“…Genome-wide DNA methylation quantitative trait locus (mQTL) analysis of human pancreatic islets has revealed 383 significant CpG sites in known diabetes loci as potential methylation targets; importantly, some of the identified candidate genes, i.e., glutathione peroxidase 7 (GPX7), glutathione S-transferase theta 1 (GSTT1), and sorting nexin 19 (SNX19) directly affect key biological processes such as proliferation and apoptosis of pancreatic islet beta cells [20]. More recently, Ye et al identified widespread genetic and epigenetic interactions at known T1D susceptibility loci; they showed (in their preprint) that DNA methylation at five loci, i.e., integrin subunit beta 3 binding protein (ITGB3BP), AF4/FMR2 family member 3 (AFF3), protein tyrosine phosphatase non-receptor type 2 (PTPN2), cathepsin H (CTSH), and cytotoxic T lymphocyte-associated protein 4 (CTLA4), is potentially causal to T1D [21]. Interestingly, it seems that some epigenetic changes may even be present years before T1D diagnosis: Johnson et al identified 10 regions of the genome in which methylation differs between T1D cases and controls from as early as birth, in some cases multiple years before T1D diagnosis [22].…”
Section: Therapies Targeting Dna Methylation In T1dmentioning
confidence: 99%